FLOUTING MAXIM ANALYSIS ON BBC RADIO 1 YOUTUBE CHANNEL â€œKIDS ASK RYAN REYNOLDSâ€ - Damiri, Adenan; Fiskaryanti, Aida; Nainggolan, Billi Andara; Amalia, Nidia (Universitas Pamulang, 2023)
This study discusses the analysis of the flouting maxim using a YouTube video on the BBC Radio 1 YouTube channel